2009
DOI: 10.1172/jci38922
|View full text |Cite
|
Sign up to set email alerts
|

Murine Jagged1/Notch signaling in the second heart field orchestrates Fgf8 expression and tissue-tissue interactions during outflow tract development

Abstract: Notch signaling is vital for proper cardiovascular development and function in both humans and animal models. Indeed, mutations in either JAGGED or NOTCH cause congenital heart disease in humans and NOTCH mutations are associated with adult valvular disease. Notch typically functions to mediate developmental interactions between adjacent tissues. Here we show that either absence of the Notch ligand Jagged1 or inhibition of Notch signaling in second heart field tissues results in murine aortic arch artery and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(187 citation statements)
references
References 55 publications
(65 reference statements)
7
176
0
Order By: Relevance
“…Interference with Notch signaling arrests cardiac development (6,(23)(24)(25). In accordance, MesP1-cre-induced mutation of RBPJ lox/lox (hereafter, "RBPJ mutant") reduced the size and compactness of the heart, as revealed by analyses of H&E-stained sections at embryonic day (E) 9.75 ( Fig.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Interference with Notch signaling arrests cardiac development (6,(23)(24)(25). In accordance, MesP1-cre-induced mutation of RBPJ lox/lox (hereafter, "RBPJ mutant") reduced the size and compactness of the heart, as revealed by analyses of H&E-stained sections at embryonic day (E) 9.75 ( Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Thus the up-regulated expression of such morphogens in double mutants also might contribute indirectly to the rescued development of nonmesoderm-derived cells (29). In previous analyses of mice that carried a conditional Jagged1 mutation or that expressed a dominant-negative Maml using Mef2c-cre also exhibit SHF morphogenesis affects and reduced Bmp and Fgf signaling (23). In contrast, in studies using Isl1-cre, elevated Wnt/ β-catenin signaling has been observed after conditional mutation of Notch1 but not RBPJ (24,25).…”
Section: Discussionmentioning
confidence: 98%
“…For example, reciprocal signaling between the second heart field and cardiac NCCs is required for proper patterning of the aortic arch arteries (Waldo et al, 2005). Deletion of Notch signaling specifically in the second heart field leads to altered NCC behavior, resulting in a decrease of NCC-derived tissue in the outflow tract and improper patterning of the arch arteries (High et al, 2009). Other NCCenriched miRNAs probably regulate similar pathways to coordinate the complex tissue-tissue interactions required to pattern the outflow tract and aortic arch arteries.…”
Section: Research Articlementioning
confidence: 99%
“…On binding with its ligand, a series of cleavage events release the Notch intracellular domain, which translocates to the nucleus and binds with its cofactors mastermind‐like protein and RBPJκ to regulate expression of target genes 14. Specifically, the Notch signaling family has been shown to play a critical role in cardiac OFT development because loss of the Notch signaling pathway, specifically in the SHF via a dominant‐negative truncated form of mastermind‐like protein or loss of Jagged1, results in a spectrum of OFT defects including aortic valve abnormalities 15. Furthermore, mutations in NOTCH2 and the Notch ligand JAGGED1 are responsible for Alagille syndrome, which is characterized by pulmonary stenosis, ventricular septal defects, coarctation of the aorta, and tetralogy of Fallot, among other developmental defects 16, 17.…”
Section: Introductionmentioning
confidence: 99%